Profile of women who carried out smoking cessation treatment: a systematic review - Pereira, Caroline Figueira; Vargas, Divane de (Revista de Saúde Pública, 2015)
OBJECTIVE: Analyze the profile of women, in health services, who carry out treatment for smoking cessation. METHODS: Systematic review that used the following sources of information: Cummulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, Biblioteca Virtual em Saúde (BVS), Scopus and Web of Science. We included quantitative studies that addressed the characterization of women, in health services, who carried out treatment for smoking cessation, resulting in 12 articles for analysis. The assessment of the methodological quality of the studies was performed using the instrument MAStARI from Joanna Briggs Institute. RESULTS: The predominant profile of women who carried out treatment for smoking cessation in health services was composed of white, married, employed, and highly level educated women. Women who carried out the treatment for smoking cessation in specialized services had a more advanced age, were white, were married and had a diagnosis of depression. The quality level of most studies was moderate. CONCLUSIONS: The profile of women who carry out treatment for smoking cessation, either in general or specialized health services, is composed of white, married, and highly level educated women. Publications about smoking women are scarce and the lack of Brazilian studies characterizing the profile of women who start treatment for smoking cessation shows the need for studies that explore this subject.